2012
DOI: 10.1002/jclp.21865
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Change in Mindfulness and Perceived Stress in a Mindfulness‐Based Stress Reduction Program

Abstract: Evidence that changes in mindfulness precede changes in perceived stress in a standard MBSR course is consistent with previous studies suggesting that improvements in mindfulness skills may mediate the effects of mindfulness training on mental health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
243
3
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(320 citation statements)
references
References 16 publications
(23 reference statements)
32
243
3
9
Order By: Relevance
“…O achado de que uma intervenção baseada na meditação pode auxiliar na redução dos níveis percebidos de estresse está em consonância com outros estudos que avaliaram tanto amostras universitárias (Carmody & Baer, 2008;Fan et al, 2014;Greeson et al, 2014;Jain et al, 2007;Oman et al, 2008;Shapiro et al, 2011), como não universitárias (Baer, Carmody, & Hunsinger, 2012). No presente estudo, a intervenção de meditação focada produziu um efeito protetivo para o estresse especialmente nas fases de resistência e quaseexaustão.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…O achado de que uma intervenção baseada na meditação pode auxiliar na redução dos níveis percebidos de estresse está em consonância com outros estudos que avaliaram tanto amostras universitárias (Carmody & Baer, 2008;Fan et al, 2014;Greeson et al, 2014;Jain et al, 2007;Oman et al, 2008;Shapiro et al, 2011), como não universitárias (Baer, Carmody, & Hunsinger, 2012). No presente estudo, a intervenção de meditação focada produziu um efeito protetivo para o estresse especialmente nas fases de resistência e quaseexaustão.…”
Section: Discussionunclassified
“…Estes resultados corroboram parcialmente achados de estudos anteriores que encontraram mudanças para a faceta descrever e não reagir em estudantes universitários após intervenções baseadas na meditação, comparado a um grupo controle (Baer et al, 2012;Bruin, Meppelink, & Bögels, 2015;Carmody & Baer, 2008). No entanto, também existem resultados com universitários que mostraram melhora em outras facetas, tal como observar, não julgar e agir com consciência (Bruin et al, 2015;Carmody & Baer, 2008).…”
Section: Carpena and Cb Menezesunclassified
See 1 more Smart Citation
“…Baer et al 2012), others have shown that not all currently measurable facets of mindfulness explain the effects of interventions on well-being (e.g. Eberth and Sedlmeier 2012;Nyklicek and Kuijpers 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Baer, Carmody, and Hunsinger (2012) examined weekly changes in self-reported mindfulness and perceived stress in participants who completed an 8-week course in mindfulness-based stress reduction (MBSR). Participants were 87 adults with problematic levels of stress related to chronic illness, chronic pain, and other life circumstances who participated in MBSR at an academic medical center.…”
Section: Post-intervention Debriefing Questions (Role Of Diversity Inmentioning
confidence: 99%